Issues of National Drug Security in Formation of a Reserve of Antibacterial Agents Intended to Eliminate Medical and Sanitary Consequences of Emergencies - L. Yu. Chernikova; V. N. Dmitruk; N. L. Denisov; E. G. Morozova; A. V. Ratkin; E. V. Karakulova (Разработка и регистрация лекарственных средств)
Introduction. The article considers the issues of forming a reserve of antibacterial agents designed to eliminate medical and sanitary consequences of emergencies from the perspective of national drug security.Aim. To determine the degree of import substitution of antibacterial agents included in the regional drug reserve.Materials and methods. We carried out a content analysis of data from regulatory documents and research papers related to formation of drug reserves, a logical and structural analysis of the range of antibacterial agents included in the reserve of the Tomsk region, and an analysis of data from the National Drug Register. In the study, we used the Anatomical Therapeutic Chemical (ATC) Classification System of drugs.Results and discussion. It was established that for 19 international nonproprietary names (INN) of antibacterial agents belonging to the group of antibacterials for systemic use (ATC code J01) and forming the reserve of the Tomsk region, 294 brand names (BN) were registered on the pharmaceutical market of the Russian Federation in 2021. The share of registered domestic BN was 49.3 %, and the degree of import dependence of domestic drug manufacturing on foreign-made active pharmaceutical ingredients (APIs) was 81.4 %. It was found that 6 Russian enterprises manufacture APIs that supply production of 10 antibacterial agents included in the drug reserve. A classification of medicines by strategic availability for replenishing the drug reserve was developed. A map on strategic availability of domestically manufactured antibacterial agents included in the reserve was drawn up.Conclusion. We demonstrated high dependence of antibacterial reserve formation on import of this group of medicines and APIs to the Russian Federation. The classification of medicines which takes into account the possibility of replenishing the drug reserve in emergency conditions and if import of medicines stops can be recommended for use by the center for disaster medicine to optimize the nomenclature of drug reserves at various levels from the perspective of national drug security promotion.